INTERDEPENDENCE of DIGITAL PLATFORMS, DEVELOPMENT of TECHNOFEUDALISM and WORK PRECARIOUSNESS in the GIG ECONOMY - Krasulja, Nevena; Ilić, Dejan; Radosavljević, Dragana; Mihajlović, Aleksandar (Journal of Economic Development, Environment and People, 2024)
The aim of this paper is to present the results of an analysis that explores the interdependence between digital platforms and development of technofeudalism and work precariousness within the Gig economy, examining how digital platforms influence the establishment of technofeudal power structures. Digital platforms have transformed traditional employment by promoting freelance work and facilitating the transition to flexible, short-term work arrangements. This model introduces significant challenges, in particular, insecurity, “algorithmic control” and a lack of worker protections. Platforms often control access to work, dictate wage structures, and retain ownership of workers’ data. By analysing case studies such as Glovo and Uber, this paper illustrates how these platforms create a system that encourages “self-exploitation” under the guise of autonomy and entrepreneurial freedom. This dynamic contributes to technofeudalism, concentrating power among platform owners who profit significantly, while workers become vulnerable and dependent on these digital systems for income. As a result, they face unstable wages, reduced autonomy, and isolation due to algorithmic management. This research advances our understanding of digital labour practices and provides a theoretical framework for interpreting power and inequality in the gig economy. It highlights the need for regulatory changes to ensure fair treatment of short-term and freelance workers.